RISIKO LIKUIDITAS BANK DAN ASSET LIABILITIES MANAGEMENT - Iwan Lesmana (Majalah Ilmiah Ekonomi Komputer, 2007)
Uquidity is of critical importance to companies in the banking services sector. Most failures of financialintermediaries have occured in large part due to insufficient liquidity resulting from adverse circumstances.Goldman Sachs has in piace a comprehensive set of liquidity and funding policies that are intended tomaintain significant flexibility to address specific and broader industry or market liquidity events.In asset liabilities mal1agement or liquidity management, liquidity risk is managed through the maturity profileof bank's funding base such that they should be able to liquidate assets prior to bank's liabilities coming due,even in prolonged or severe liquidity stress.A liquidity problem in banking may have implications on the entire banking system, so an analysis of liquiditymanagement cannot be limited, but it must examine how the liquitdity requierements can develop in variousscenario. The scenario is defined in two different periode; short term (basic surplus), or long term (liquidityratio, liquidity index and loan to deposit ratio). Estimation of the liquidity position shail be performed bycalculating the liquid(ty mismatch according to repayment period and the ratio of the liquid assets to liabilitiesfor a repayment period.Applying liquidity management, a bank must have adequate information systems for measuring, monitoring,controlling and reporting liquidity risk on a timely basis.Key word; intermediary, liquidity risk and asset & liabilities management.